2013
DOI: 10.4274/tpa.235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of food allergy in nursery and kindergarten children in Samsun

Abstract: SummaryAim: In recent years, the frequency of food allergy in children has gradually increased. Food allergy affects growth, development and quality of life adversely. There is no enough research in the preschool age group in which food allergy is observed more frequently. In this study, we investigated the prevalence of food allergy in nursery and kindergarten children living in Samsun. Material and Method: Nursery and kindergarten children living in Samsun were included in this study. A standardized self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In previous studies it has been reported that chest nut and cashew nut allergies were the most common type in USA and Brasilia while hazel nut and chest nut were common in European countries (8). In accordance with previous studies from our country and other countries hazel nut and chest nut allergies were the most common TNAs in our study (9,10).…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies it has been reported that chest nut and cashew nut allergies were the most common type in USA and Brasilia while hazel nut and chest nut were common in European countries (8). In accordance with previous studies from our country and other countries hazel nut and chest nut allergies were the most common TNAs in our study (9,10).…”
Section: Discussionsupporting
confidence: 92%
“…Putting together the number of reports (and studies) included in the first systematic review from EAACI, with the records screened and included for the current review (September 2012 to June 2021), the total number of reports included was 147, which were based on 110 studies. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ,...…”
Section: Resultsmentioning
confidence: 99%
“…2,7,8 There is no prevalence study on food allergy in children covering the entire country of Turkey. In some studies conducted in Turkey regarding the prevalence of food allergy in children, red meat allergy was rarely reported, [9][10][11] while in others it was frequently reported. 12,13 The conflicting results may be due to the fact that these studies were conducted in different regions of Turkey.…”
mentioning
confidence: 99%